Intratumoral Fibrosis and Tumor Growth Pattern as Prognostic Factors in Optimally Resected Pancreatic Neuroendocrine Neoplasms: An Analysis of 168 Cases. Issue 2 (February 2020) - Chatterjee, Deyali; Trikalinos, Nikolaos A.; Williams, Greg A.; Liu, Jingxia; Hawkins, William G.; Hammill, Chet
Abstract : Objectives: Pancreatic neuroendocrine neoplasms (PanNENs) can recur after curative resection. We sought to establish the significance of tumor fibrosis and tumor growth pattern as predictors of recurrence-free survival and overall survival. Methods: A retrospective query of an institutional surgical database was performed from 2000 to 2018 to identify optimally resected PanNENs. All eligible slides were reviewed by an experienced gastrointestinal pathologist for established histopathologic prognostic factors, as well as fibrosis and tumor growth pattern. We evaluated the effect of the interested variables through Cox proportional hazards models. Results: One hundred sixty-eight cases were considered. The majority of patients (90%) had grade 1 or 2 tumors, 46% showed significant fibrosis, and 22% demonstrated an infiltrative growth pattern. Twenty-one percent of patients had a recurrence. In multivariable analysis, lymphovascular invasion with a hazard ratio (HR) of 5.1 and infiltrative growth pattern (HR, 2.8) were significantly associated with increased risk of recurrence and increased risk of death (HR, 3.6 and 2.7, respectively). There was a significant decrease in recurrence-free survival and overall survival for fibrosis and infiltrative growth pattern. Conclusions: In optimally resected PanNENs, the presence of fibrosis and infiltrative growth pattern are significant risk factors for recurrence and/or decreased survival.